Duration and magnitude of postoperative risk of venous thromboembolism after planned inguinal hernia repair in men: a population-based cohort study - Humes, D.J.; Abdul-Sultan, Alyshah; Walker, Alex J.; Ludvigsson, Jonas F.; West, Joe (Springer Verlag, 2018)
Purpose Little is known regarding the magnitude and timing of the risk of VTE following inguinal hernia surgery. We aimed to determine the absolute and relative rates of venous thromboembolism (VTE) following planned inguinal hernia repair. Methods We analysed male adults with a first inguinal hernia repair with no prior record of VTE from the Clinical Practice Research Datalink, linked to the Hospital Episode Statistics (2001–2011). Crude rates and adjusted hazard ratios (HR) of the first VTE were calculated using Cox regression analysis to compare specific time periods following the surgery compared to the general population. Results We identified 28,782 men who underwent an inguinal hernia repair with 53 (0.18%) having a first VTE in the 90 days following surgery. The overall rate of VTE in the first 90 days following surgery was 7.61 per 1000 person years (pyrs) (95% CI 5.82–9.96). Increasing age, a body mass index > 30 kg/m2 and an in-patient procedure were associated with an increased risk of VTE, when compared to the general population. The risk of VTE was highest in the 1st month following the surgery with a 2.3- (aHR 2.33; 95% CI 1.09–4.99) and 3.5- (aHR 3.47; 95% CI 2.07–5.83) fold increased risk compared to the general population for both day case and planned in-patient procedures, respectively. Conclusions Reassuringly, the absolute rates of VTE following inguinal hernia repair are low. Patients should be informed that their peak risk of VTE is during the 1st month following the surgery. Further studies on the optimum duration of thromboprophylaxis following surgery are required in high-risk patients undergoing hernia repair.